MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN AKIDAH AKHLAK - Nur Huda (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2023)
The current decentralized education system provides an opportunity for every educational institution to improve the quality and quality of schools by implementing School Based Management (SBM). MI Ulumiyah Pare as an educational institution participates in responding to improving the quality of education by seeking every teacher to be creative in improving appropriate classroom management so that learning runs efficiently and effectively. This Classroom Management Concept seeks to provide solutions to problems in class, whose scope is not only limited to delivering material, but includes several things that are comprehensive for organizing classes, including academic activities in the form of planning, implementing and assessing learning. administrative activities which include procedural and organizational activities such as room arrangement, grouping of students in the division of tasks, enforcement of class discipline, procurement of tests, class organization, Analysis is carried out with, data reduction, classifying and centralizing data that has been obtained in the field to facilitate researchers and obtained data. collect data in an organized way by giving the possibility of conclusions and actions. The results of research on class management in order to increase the effectiveness of teaching Akidah Akhlak MI Ulumiyah Pare, show "that class management can indeed increase the effectiveness of learning Akidah Akhlak MI Ulumiyah Pare". Classroom management is important in increasing the effectiveness of learning.